A Study on Reasons for Depleting Participation of Shareholders in Meetings: A Pathway Towards Effective Participation - B, LEELESH SUNDARAM.; R, SORNALAKSHIMI R.; GAYATHRI, R.; PRIYA, V. VISHNU (The journal of contemporary issues in business and government, 2020)
A shareholder is considered as an investor and as a member of the company for the amount of capital that is contributed by him towards the company. The company has seen or perceived it as that the shareholder is a partner in the company and has taken various steps with respect to consideration and contemplations of the shareholders in the business entity. various studies has tried to identify the relationship between the companies and shareholders, research has failed to note or recognize the reason in the recent reduction in participation of shareholders in meetings, therefore a ambiguity comes into the glare of limelight with respect to the reasons for reduction in the participation ratio and it is curious note and identify whether there is any relationship that exist between the above stated problem and share investment, because it could be understood from company annual reports that investors with high share investment are given high priority in company decisions. Thus this research is carried out with a motive to identify the reasons for depletion in the rate of participation of shareholders in company meetings. by virtue of non-probability convenience sampling method it could be found out that there is no relationship between the number of share investment and lack of protection of interest of shareholders as poor reason for poor participation in meeting and there is no relationship between the number of share investment and lack of protection of interest of shareholders as poor reason for poor participation in meetings. Thus the study recommends that that the companies must take necessary steps for purpose of protection of interest of shareholders. The shareholders must also be motivated to ensure participation.